Acute abdominal pain in athletes - diagnostic challenges and indications for surgical intervention: A Narrative Review - Wijas, Daniel; Olszok, Mikołaj; Kluś, Michał; Kozdra, Bartłomiej; Makselan, Natalia; Nawrat, Natalia; Handzel, Karolina; Anczyk, Antoni; Karbowiak, Krzysztof (Quality in Sport, 2026)
Background: Abdominal and groin pain in athletes is diagnostically challenging due to overlapping causes including exercise-related gastrointestinal symptoms, musculoskeletal injuries, and serious intra-abdominal pathology. Aim: To explore the diagnostic complexity, emphasize the importance of multidisciplinary management, and discuss clinical implications for athletes presenting with abdominal or groin pain. Methods: Review of clinical studies assessing diagnostic approaches, reliability of physical examinations, imaging techniques, and treatment outcomes in athletes with lower abdominal or inguinal pain. Results: Exercise-induced transient abdominal pain (ETAP) and athletic pubalgia are common conditions causing pain that mimics more serious pathology; clinical examination tests show variable but generally acceptable reliability; imaging modalities such as ultrasound, MRI, and CT improve diagnostic accuracy; multidisciplinary collaboration among sports physicians, surgeons, radiologists, and physiotherapists enhances management; surgical interventions targeting pelvic floor or abdominal wall defects yield high rates of return to sport in selected athletes; however, literature is limited by heterogeneous populations and lack of standardized diagnostic criteria. Conclusions: Early and accurate diagnosis of abdominal and groin pain in athletes requires careful clinical assessment supported by appropriate imaging and a multidisciplinary approach to optimize outcomes. Further research is needed to establish standardized diagnostic guidelines and treatment protocols tailored to athletic populations.